Therapeutic Potential of Carnosic Acid in Alopecia: A Mechanistic Perspective - Singh, Priyanka; Kushwaha, Poonam; Ahmad, Mohammad; Husain, Atif (Planta Medica, 2025)
Alopecia, characterised by partial or complete hair loss, significantly affects the psychological and social well-being of individuals. Current FDA-approved treatments, such as topical minoxidil and oral finasteride, often present limitations, including skin irritation and suboptimal efficacy, compromising patient adherence. In recent years, natural compounds have garnered attention as potential alternatives, with carnosic acid emerging as a promising candidate due to its multifaceted biological activities. Carnosic acid, a diterpenic polyphenol predominantly found in rosemary (Rosmarinus officinalis) and sage (Salvia officinalis), exhibits potent antioxidant, anti-inflammatory, anti-androgenic, neuroprotective, and hair follicle-regenerative properties. Despite its therapeutic potential, its poor solubility and stability in conventional formulations limit its clinical application. This review comprehensively explores the mechanisms through which carnosic acid exerts its effects in alopecia management, focusing on its antioxidant capacity, anti-inflammatory responses, inhibition of dihydrotestosterone activity, promotion of hair follicle regeneration, and neuroprotective actions. The findings highlight carnosic acidʼs potential as a natural, effective, and safer alternative for alopecia treatment.
Keywords: alopecia; carnosic acid; Lamiaceae Rosmarinus officinalis; Salvia officinalis antioxidant; anti-inflammatory; anti-androgenic; hair follicle regeneration